Occurence of urinary tract infections in type 2 diabetes mellitus patients taking sodium-glucose co-transporter-2 (SGLT-2) inhibitors to regulate their blood sugar levels - Ashfaq, Mahnoor; Shafique, Sadia; Niazi, Zenab; Shah, Syed Yasir; Memon, Siraj; Qureshi, Kashifa; Banaras, Faizan (International journal of health sciences, 2023)
Background and Aim: The occurrence of urinary tract infection (UTI) in type 2 diabetes (T2DM) administered with sodium-glucose co-transporter-2 (SGLT2) inhibitors are still debatable. The present study aimed to assess the occurrence of UTI in T2DM patients taking SGLT-2 inhibitors to regulate their blood sugar levels. Patients and Methods: This cross-sectional study was carried out on 369 T2DM patients investigated in the Nephrology division of Khyber Teaching Hospital, Peshawar from January 2022 to December 2022. Dapagliflozin and empagliflozin were SGLT-2 inhibitors drugs given to each individual. Patient’s detailed history and genitourinary infections were noted from medical records. Pain during micturition, micturition urgency, redness, abdominal pain, vomiting, and frequency of micturition, fever, soreness, and diarrhea were recorded using questionnaire based proforma. Results: Of the total 369 patients, the frequency of patients administered with dapagliflozin and empagliflozin was 178 (48.2%) and 191 (51.8%) respectively. Among 178 patients, there were 112 (62.9%) male and 66 (37.1%) females. Among 191 patients, there were 136 (71.2%) male and 55 (28.8%) females. The occurrence of UTIs in patients using dapagliflozin and empagliflozin was 18 (10.1%) and 28 (14.7%) respectively. Likewise, the genital tract infections were found in 20 (11.2%) dapagliflozin users and 26 (13.6%) empagliflozin users.